Board Diversity, Koneksi Politik dan Financial Distress - Kharis, Jassica Brigita; Nugrahanti, Yeterina Widi (E-Jurnal Akuntansi; Vol 32 No 8 (2022), 2022)
This study aims to determine the effect of board diversity (gender diversity, educational background, proportion of independent boards) and political connections on financial distress. Altman Z-Score is used to measure financial distress. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The data analysis technique used in this study is panel data regression using data processing software Eviews 12. The results show that gender diversity and political connections have a negative effect on financial distress. While educational background has a positive effect on financial distress. The test results also show that the proportion of independent boards has no effect on financial distress. Keywords: Financial Distress; Boards Diversity; Political Connection; Z-Score.